Emergent Issues and Vulnerability Factors in Temporary and Intermediate Shelters following the 2015 Nepal Earthquake. Issue 3 (November 2016) - Khazai, Bijan; Girard, Trevor; Brink, Susan; Anhorn, Johannes; Jimee, Ganesh Kumar; Parajuli, Bhubaneswari; Wagle, Sarad; Khanal, Omkala
The 25 April 7.8 magnitude Gorkha earthquake and subsequent aftershocks, including the 7.3 magnitude earthquake in Dolakha, severely damaged or destroyed nearly 900, 000 buildings and approximately 2.3 million people continue to be displaced. We conducted 284 household surveys in 177 shelter sites spanning 27 Municipalities/VDCs and 7 districts. The aim of the survey was to analyze the shelter response situation in both urban and rural areas with a view on emerging factors influencing the decision processes of displaced households seeking shelter and temporary housing. It was found that in-place sheltering close to damaged homes was favored by many residents in both urban and rural areas as many preferred to stay close to their homes, food reserves, livelihoods and social ties. The experience from this event shows that spontaneous sheltering behavior and participatory management of these sites should be accommodated and supported in the shelter response strategy.